2009
DOI: 10.1007/s00595-008-3946-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibroma adjacent to the thyroid gland and a thyroid papillary carcinoma in a patient with neurofibromatosis type 1: Report of a case

Abstract: Neurofibromatosis (NF) type 1, also known as von Recklinghausen's disease, is an autosomal-dominant inherited disorder. Some tumors may develop in these patients, including optic pathway gliomas, astrocytomas, brainstem gliomas, chronic myeloid leukemia, and rhabdomyosarcoma. Patients with neurofibromatosis type 1 show also an increased risk of endocrine tumors, especially pheochromocytomas, whereas thyroid carcinoma is very rare. It is also rare for a neurofibroma to arise in the tissue neighboring the thyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…NF1 has been reported to be associated with a number of malignancies. However, the occurence of papillary thyroid carcinoma associated with NF1 is very rare, with only four cases having been published in the English literature (24)(25)(26)(27). Furthermore, the coexistence of NF1, GIST, pheochromocytoma and papillary thyroid carcinoma has not been previously reported.…”
Section: Discussionmentioning
confidence: 96%
“…NF1 has been reported to be associated with a number of malignancies. However, the occurence of papillary thyroid carcinoma associated with NF1 is very rare, with only four cases having been published in the English literature (24)(25)(26)(27). Furthermore, the coexistence of NF1, GIST, pheochromocytoma and papillary thyroid carcinoma has not been previously reported.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of thyroid cancer is rapidly increasing in South Korea, and most cases are PTC. The high rates of incidence of RET/PTC rearrangements or point mutations in RAS and c-MET oncogenes are genetic hallmarks of PTC [3]. The BRAF kinase is a serine-threonine kinase that mediates signal transduction through the MEK-ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ras GTPases interact with multiple pathways, including the RAF-MEK-ERK mitogen-activated protein kinase pathway. Mutations in the NF1 gene result in abnormal cell growth and in the formation of benign and malignant tumors [3]. Because BRAF V600E mutation and NF1 gene mutation are both involved in the MEK-ERK pathway, Koksal et al [3] suggested that the development of PTC in patients with NF1 may be associated with the ras gene but that further evidence is necessary to confirm this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased instances of non-medullary thyroid carcinoma in patients with NF1 have been described in the literature [5]. However, NF1 association with papillary thyroid carcinoma (PTC), one of the most common endocrine malignancies, is exceedingly rare [6].…”
Section: Introductionmentioning
confidence: 99%